Suffering Women and their Skin(s) : Representations of Female Bodies in Pain in Euripides - Kousoulini, Vasiliki (Synthesis.)
In ancient Greek tragedy, the physical pain of male bodies is often depicted. Nonetheless, there are only a few examples of female bodies in pain. Tragic heroines rarely or never refer to their somatic anguish. In the Euripidean corpus, this pain is narrated by male and female Messengers. These Messengers in Alcestis, Medea, and Hecuba, describe the gestures and the miens of the heroines in pain with great detail. Special attention is paid to the skin of these women. This paper examines the gestures of these suffering heroines as responses to physical sources of pain, such as torment by the accumulation of excessive fluids under the skin, the eating of skin and flesh by poison, and the piercing of the skin by sharp objects.